Cooperation of augmented calcium sensitization and increased calcium entry contributes to high blood pressure in salt-sensitive Dahl rats - Zicha, Josef; Behuliak, Michal; Vavřínová, Anna; Dobešová, Zdenka; Kuneš, Jaroslav; Rauchová, Hana; Vaněčková, Ivana (Hypertension research, 2021)
Salt hypertensive Dahl rats are characterized by sympathoexcitation and relative NO deficiency. We tested the hypothesis that the increased blood pressure (BP) response to fasudil in salt hypertensive Dahl rats is due to augmented calcium sensitization in the salt-sensitive strain and/or due to their decreased baroreflex efficiency. BP reduction after acute administration of nifedipine (an L-type voltage-dependent calcium channel blocker) or fasudil (a Rho kinase inhibitor) was studied in conscious intact rats and in rats subjected to acute NO synthase inhibition or combined blockade of the renin-angiotensin system (captopril), sympathetic nervous system (pentolinium), and NO synthase (L-NAME). Intact salt-sensitive (SS) Dahl rats fed a low-salt diet had greater BP responses to nifedipine (-31 ± 6 mmHg) or fasudil (-34 ± 7 mmHg) than salt-resistant (SR) Dahl rats (-16 ± 4 and -17 ± 2 mmHg, respectively), and a high-salt intake augmented the BP response only in SS rats. These BP responses were doubled after acute NO synthase inhibition, indicating that endogenous NO attenuates both calcium entry and calcium sensitization. Additional pentolinium administration, which minimized sympathetic compensation for the drug-induced BP reduction, magnified the BP responses to nifedipine or fasudil in all groups except for salt hypertensive SS rats due to their lower baroreflex efficiency. The BP response to the calcium channel blocker nifedipine can distinguish SS and SR rats even after calcium sensitization inhibition by fasudil, which was not seen when fasudil was administered to nifedipine-pretreated rats. Thus, enhanced calcium entry (potentiated by sympathoexcitation) in salt hypertensive Dahl rats is the abnormality that is essential for their BP increase, which was further augmented by increased calcium sensitization in salt-sensitive Dahl rats.
Keywords: Calcium; Sympathetic tone; hypertenze; Rho kinase; potkani inbrední Dahl; vápník; Voltage-dependent calcium channels; Baroreflex efficiency; Hypertension; Rats, Inbred Dahl; Vasoconstriction; Sodium Chloride, Dietary; krysa rodu Rattus; Animals; Nifedipine; krevní tlak; zvířata; Rats; Blood Pressure; Nitric oxide; kuchyňská sůl; vazokonstrikce; Fasudil